2005
DOI: 10.1007/s10822-005-7928-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Molecular Similarity from MST Fractional Contributions to the Octanol/water Partition Coefficient

Abstract: The use of a recently proposed hydrophobic similarity index for the alignment of molecules and the prediction of their differences in biological activity is described. The hydrophobic similarity index exploits atomic contributions to the octanol/water transfer free energy, which are evaluated by means of the fractional partitioning scheme developed within the framework of the Miertus-Scrocco-Tomasi continuum model. Those contributions are used to define global and local measures of hydrophobic similarity. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…QM-based continuum solvation methods are a promising strategy for deriving 3D descriptors, such as COSMO-RS-based σ-profiles [78][79][80][81] or MST-derived 3D lipophilicity patterns [82][83][84][97][98][99], which in turn may be exploited in computer-aided drug design. The set of studies reported up to now for a variety of benchmark datasets, covering both measurements of molecular similarity for aligned compound or the derivation of 3D-QSAR models, are encouraging.…”
Section: Final Consideration and Perspectivesmentioning
confidence: 99%
“…QM-based continuum solvation methods are a promising strategy for deriving 3D descriptors, such as COSMO-RS-based σ-profiles [78][79][80][81] or MST-derived 3D lipophilicity patterns [82][83][84][97][98][99], which in turn may be exploited in computer-aided drug design. The set of studies reported up to now for a variety of benchmark datasets, covering both measurements of molecular similarity for aligned compound or the derivation of 3D-QSAR models, are encouraging.…”
Section: Final Consideration and Perspectivesmentioning
confidence: 99%
“…In this work, following our previous studies on hydrophobic similarity, the QM/MST‐based hydrophobic contributions have been utilized as physicochemical descriptors suitable for 3D‐QSAR studies. By combining the electrostatic and nonelectrostatic components of the octanol/water partition coefficient, which can obtained through a suitable partitioning of the solvation free energy, the 3D‐QSAR models derived for the five molecular systems have a predictive accuracy that compares well with standard CoMFA and CoMSIA techniques.…”
Section: Final Remarksmentioning
confidence: 99%
“…The success of these strategies is dependent not only on the robustness of LB and SB techniques, but also on the synergy and complementarity of the molecular descriptors encoded in these methods, and the mathematical formalism adopted to combine them into a ranking function that alleviates the potential deficiencies of these methods. , Here, we address these questions by examining the performance of parallel and hybrid approaches to discriminate between active and inactive compounds in the VS of chemical libraries. To this end, attention is paid to the use of lipophilic (Hyphar) descriptors, which have been examined in the context of 3D-QSAR studies , and similarity measurements of molecular overlays . The lipophilic descriptors are based on the atomic decomposition of the global lipophilicity of a given compound estimated from quantum mechanical (QM) continuum solvation calculations in water and n -octanol, yielding a 3D lipophilicity distribution of the molecule. , In this work, the Hyphar-based similarity measurements have been exploited in conjunction with three docking programs: rDock, GOLD, and Glide. In particular, we have evaluated the synergy between these LB and SB techniques to enhance the performance of VS through the analysis of new rankings obtained by using different parallel and hybrid combination strategies.…”
Section: Introductionmentioning
confidence: 99%